Polemika o plagiatu ali kako je nastajal postmodernizem v Jugoslaviji - Uršič, Julija (Primerjalna književnost, 2006)
A polemics on plagiarism or the origins of post-modernism in Yugoslavia. When Kiš published his Grobnica za Borisa Davidoviča (A Tomb for Boris Davidovič) in 1976, a critic's allegation that the book was a work of plagiarism initiated "one of the biggest literary scandals" in the former Yugoslavia. This essay takes a brief look at plagiarism through time, before turning to the actual case of Danilo Kiš and attempting to determine the role that the polemics played in a new understanding of literary and social reality.
Keywords: Kiš, Danilo, 1935-1989; srbska književnost; polemike; postmodernizem; plagiati; avtorstvo